The Influence of Information Literacy Learning and Problem-based Learning on Students’ Learning Outcome in Social Science Subject at Public Junior High School 2 of Kendit in Situbondo - Mohamad Na'im; Boiman (Future Science, 2021)
The objectives of this study are aimed at: 1) analyzing the effect of Information Literacy Learning model on the learning outcome of eighth-grade students of Public Junior High School 2 of Kendit in Situbondo in social science subject; 2) analyzing the effect of Problem-based Learning model on the learning outcome of eighth-grade students of Public Junior High School 2 of Kendit in Situbondo in social science subject; 3) analyzing the differences in the learning outcome of eighth-grade students of Public Junior High School 2 of Kendit in Situbondo between the application of the Information Literacy Learning model and Problem-based Learning. This research is a correlational study. Based on the results of data analysis, the study has drawn several conclusions. First, there is a very significant influence, marked at 53.7%, of the Information Literacy Learning on learning outcome. Second, there is a significant effect of the Problem-based Learning on learning outcome, as evinced by a correlation magnitude of 57.7%. Third, the analysis has identified no significant difference between Information Literacy Learning and Problem-based Learning on learning outcome shows. This shows that both learning models are equally well applied to improve learning outcome.